INCOME SMOOTHING WITH PROFITABILITY AS AN INTERVENING VARIABLE: FINANCIAL LEVERAGE AND COMPANY SIZE - Dodi Suryadi; Olandari Mulyadi; Try Ayu Parwati (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
The research method used in this study uses multiple linear regression analysis methods. The tests carried out in this study were the classical assumption test, descriptive test, path analysis and hypothesis testing. The test equipment used in this study was the IBM SPSS Statistics application version 25. The sample in this study were 51 manufacturing companies. The selection of this research sample was based on purposive sampling with the aim of obtaining a representative sample according to predetermined criteria. The results obtained are that there is no effect of financial leverage on profitability with a significant value of 0.629. There is no effect of company size on profitability with a significant value of 0.196. There is a financial leverage effect on income smoothing with a significant value of 0.000. There is no effect of company size on income smoothing with a significant value of 0.288. There is a profitability effect on income smoothing with a significant value of 0.00. There is an indirect effect of financial leverage through profitability on income smoothing. There is an indirect effect of company size through profitability on income smoothing.